Socioeconomic Status May Impact Functional Outcome of Deep Brain Stimulation Surgery in Parkinson's Disease. Issue 1 (15th June 2015) - Genc, Gencer; Abboud, Hesham; Oravivattanakul, Srivadee; Alsallom, Faisal; Thompson, Nicolas R.; Cooper, Scott; Gostkowski, Michal; Machado, Andre; Fernandez, Hubert H.
Abstract : Objectives: To investigate the association between socioeconomic status and deep brain stimulation (DBS) outcomes in Parkinson's disease (PD). Materials and Methods: We analyzed a cohort of PD patients who underwent DBS from 2007 to 2011, who had Clinical Global Impression Scale‐Improvement subscale (CGI‐I) scores at approximately one year postsurgery. We also analyzed a subgroup of patients who had pre and postoperative Movement Disorders Society‐Unified Parkinson's Disease Rating Scale (MDS‐UPDRS) Part II (functional subscale) and European Quality of Life Scale (EQ5D) scores. We performed regression analyses to determine the association between their median household income and their improvement in the MDS‐UPDRS Part II, EQ‐5D, and CGI‐I post‐DBS surgery. Results: We analyzed 125 PD patients with CGI‐I at one year post‐DBS, including a subset of 43 patients who had pre‐ and post‐DBS MDS‐UPDRS Part II and EQ5D scores at 6 and 12 months. Median income was not significantly associated with the one‐year CGI‐I, the six‐month MDS‐UPDRS II, and the six‐month and one‐year EQ5D score. However, after adjusting for preoperative MDS‐UPDRS II score, for every 10, 000 increase in household median income, there was a 2.15‐point improvement on the MDS‐UPDRS II score after one year (95% confidence interval = −3.63 to −0.66, p = 0.0060). Conclusions: PD patients with higher household incomes had better functional improvement at one year. However, this did not necessarily translate to better quality of life or overall clinical improvement when compared with PD patients with lower household incomes. The influence of household income on DBS and other advanced therapies for PD will need further investigation.